Organic dust exposure in veterinary clinics: a case study of a small-animal practice in Portugal - Viegas, Carla (2018)
IPL/2016/CYTO_VET_ESTeSL. FCT_02/SAICT/2016 – Project nº 23222. CESAM (FCT_UID/AMB/50017/2013). FEDER (POCI-01-0145-FEDER-00763).